Kinematics Analysis of Ship Welding Robot with Variable Topology Structure - Zhengqiang Guo; Yuchen Pan; Xuepeng Yuan; Haibo Huang; Hongzhou Wang (Jixie chuandong)
A ship welding robot with variable topology structure is designed， which can change the numbers of its components to achieve the change of degree of freedom(DOF)， and to accomplish specific welding tasks such as complex welding， simple partial welding， horizontal welding and vertical welding， etc. Based on the theory of kinematic chain loop and Newton-Raphson method， the kinematics model of the mechanism is established， and the forward position solution is obtained. Then the law of velocity and acceleration is analyzed. Finally， the simulation result shows that the newly designed manipulator can meet the requirements of ship welding effectively.